(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2020)
Measuring maintainability early in the software development life cycle mainly at design phase is a landmark of crucial significance to software designers, developers and quality controllers. Initial Measurement of object oriented software maintainability, absolutely at design phase supports designers to increase their designs before the coding starts. Practitioners and developers repeatedly advocate that maintainability Measurement should be planned at design phase of development life cycle. This paper proposes a Maintainability Measurement Model that works at design phase of system development life cycle. Furthermore, statistical test is performed to justify the correlation of Maintainability with its key contributors Modifiability and Analyzability. The developed model has been authenticated using investigational tryout. In decision, it contains the empirical authentication of the developed maintainability measurement model.